Konsep Diri dengan Mekanisme Koping pada Mahasiswa Tingkat Akhir - Sisilia Bawele; Helly M. Katuuk; Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
The concept of self plays an important role in determining how individuals assess and cope with various pressures.Efforts to cope with experienced stress sources, students can employ various methods as their coping mechanisms.The aim of this study is to determine the relationship between self-concept and coping mechanisms among final-year students at Muhammadiyah University of Manado.The research uses a cross-sectional design.The sample in this study consisted of 54 respondents using the purposive sampling technique.Data collection on self-concept and coping mechanisms was conducted using a questionnaire, and analyzed using the chi-square statistical test.The results of the self-concept study showed that the majority fell into the good category, with 44 respondents (81.5%), while the majority of coping mechanisms fell into the adaptive category, with 37 respondents (68.5%).The results of the chi-square test showed a p-value of 0.007, which is < α 0.05.Conclusion: There is a relationship between self-concept and coping mechanisms among final-year students at Muhammadiyah University of Manado.